Ethical Philanthropy in the era of Patient-Centric, Value-Based Health Care - Kalina, Peter (Archives of Business Research, 2020)
Patient-centered, value-based health care implies care that is high-quality, responsive to patient preferences, delivered safely, and at a fair cost. The future of healthcare portends changes; including less favorable payer mix, decreased reimbursement and alternate compensation models. Innovative strategies will be required to maintain excellence in care while efficiently maximizing existing capital and human resources. Successfully implementing a health care institution’s initiatives cannot be achieved entirely from within. Philanthropy must fill gaps to help support research, education and clinical missions. Strong physician – patient relationships are essential to facilitating philanthropic gifts from grateful patients. While we assume magnanimous intentions and motivations, gifts may potentially influence behavior. While VIP care for patients who donated (or believed likely to) is a successful strategy; distinctions are needed between development and clinical relationships. Philanthropy cannot affect care, which must be irrespective of wealth or position. The highest professional and ethical standards and practices must be maintained when accepting grateful patient philanthropy. Developing and promoting a sustainable philanthropic strategy begins with reviewing needs and goals to support the mission; motivated and inspired by improving outcomes. Achieving missions in health care requires dedicated philanthropic partnerships. Pursued with professionalism, thoughtfulness and integrity; philanthropy represents a vital pathway to innovatively advance patient care. Support allows donors to make an investment and express their values. Realizing the direct and lasting impact of collaboration provides rewarding benefit and meaningful recognition.